Repeated metal ion measurements and long-term outcome of Durom/MMC total hip arthroplasty - Pietiläinen Sakari; Smedberg Erno; Laaksonen Inari; Venäläinen Mikko S; Lankinen Petteri; Mäkelä Keijo T (Medical Journals Sweden, 2022)
Background and purpose — Data regarding long-term behavior of metal ion levels in metal-on-metal total hip arthroplasty (MoM THA) patients is scarce. Therefore, we assessed whether there is any change in whole blood (WB) chromium (Cr), and cobalt (Co) ion measurements in Durom and MMC MoM THA patients over time. The secondary aim was to report the clinical outcomes using these devices in a single district.
Patients and methods — Durom and MMC cups were used in 249 MoM THAs from 2005 to 2011 in our district. Median follow-up time was 12 years for Durom THA (interquartile range [IQR] = 3) and 9 years for MMC THA (IQR = 1). A random coefficient model was used to compare individual differences in repeated WB Cr and Co ion measurements. The Kaplan–Meier estimator was used to analyze implant survival with any reason for revision as the endpoint.
Results — Geometric means of Cr in Durom THA and MMC THA patients decreased from 2.2 ppb (geometric standard deviation [SD] = 1.9) to 1.5 ppb (geometric SD = 2.5, p< 0.001) and from 1.8 ppb (geometric SD = 1.8) to 1.1 ppb (geometric SD = 2.8, p = 0.01) respectively. The geometric means of Co values remained unchanged. The 10-year survival of Durom THA was 82%, and that of MMC THA 89% for any revision reason as endpoint.
Interpretation — WB Cr levels decreased over time, and Co levels remained unchanged at long-term follow-up. Despite this we recommend continuing the follow-up of these devices due to relatively low implant survival.